Interdisciplinary reading of "Shiraz" and "Farewell to Shiraz" based on Westphal's theory - Mahmoud Kamali (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Using the interdisciplinary approach of geocriticism and especially its triple elements from Westphal's view, i.e. Multifocalization, Polysensoriality, and stratigraphic vision, two different types of literature, namely novel (Shiraz, a novel by Hamburger) and memoir (Farewell Shiraz by Kadivar) are investigated and analyzed. The investigation of the multifocalization shows that the recognition of Shiraz, is better done in the light of two local and foreign views, and a unipolar view of the place interferes with its complete knowledge. also, the analysis of the Polysensoriality shows that despite the soundscapes and the representation of the place using the sense of smell, the visual representation dominates in both works, however, the most complete type of representation is possible by using different senses. The third is stratigraphy, which pays attention to the time in recognizing and correctly representing the place, by showing the different time stratum in Shiraz that are well represented in both works, shows the adherence of cultural, historical and environmental factors in shaping the unique character of Shiraz and gives it a postmodern view. As well, the findings of the research show the high accuracy of representation, i.e. the presence of real references in novel Shiraz despite its fictional nature.